THE SOCIAL IMPACT OF VOLUNTARY ACTIONS PROMOTED BY LOCAL BUSINESSMEN IN VULNERABLE COMMUNITIES (International Seven Journal of Multidisciplinary, 2025)
This article investigates the social impact of voluntary actions promoted by local entrepreneurs in vulnerable communities, highlighting the potential of such initiatives to reduce inequalities and strengthen business–society relations. The research, qualitative and exploratory in nature, is based on an integrative literature review and document analysis of both Brazilian and international experiences. The findings reveal that volunteer initiatives led by local companies can generate interconnected benefits at community, organizational, and individual levels when guided by planning, active listening, and cross-sector collaboration. Case studies from Copasa and a cooperative in southern Brazil, as well as examples from Poland and Finland, demonstrate the ability of business leaders to act as agents of territorial transformation even with limited resources. The discussion supports the notion that corporate volunteering can serve as a legitimate channel for social regeneration, especially when rooted in shared objectives and ongoing impact evaluation. This study contributes to the conceptual delimitation of corporate volunteering, offers practical criteria for action, and outlines a future research agenda focused on fieldwork with small and micro enterprises.